78.8k views
5 votes
F(x)=
√(x+4) and g(x)=
x^(2)

find f(g(-6)

User Eglease
by
5.6k points

1 Answer

3 votes

Answer:


f(g(-6))=2√(10)

Explanation:

first we need to find g(-6)


g(x)= x^2\\\\g(-6)=(-6)^2\\\\g(-6)=36

so g(-6)=36

so we need to find f(36)


f(x)=√(x+4) \\\\f(36)=√(36+4) \\\\f(36)=√(40)\\\\f(36)=√(4)* √(10) \\\\f(36)=2√(10)

so that's answer


f(g(-6))=2√(10)

User Nachocab
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.